Political Conflict in Diodorus Siculus: The Χαριέστατοι and the Historian’s Moral Agenda - Barbato, Matteo (Histos, 2024)
This article investigates the historiographic identity of Diodorus through the analysis of select narratives of political conflict. These feature in sections of the Library based on different sources and are structured around the contrast between a group of political actors labelled as the χαριέστατοι and another to which they are opposed. I show that, whatever the respective position of the factions on the socio-political spectrum, the main role of the χαριέστατοι is to act as the mouthpieces of Diodorus’ moralising. I also argue that Diodorus’ use of this pattern was the result of his engagement with an Aristotelian variant of traditional aristocratic thought, which he adapted to the political scenarios recounted by his sources in order to suit his moral agenda.